2017
DOI: 10.1093/bja/aex100
|View full text |Cite
|
Sign up to set email alerts
|

Routine use of viscoelastic blood tests for diagnosis and treatment of coagulopathic bleeding in cardiac surgery: updated systematic review and meta-analysis

Abstract: Viscoelastic point-of-care tests are commonly used to provide prompt diagnosis of coagulopathy and allow targeted treatments in bleeding patients. We updated existing meta-analyses that have evaluated the clinical effectiveness of viscoelastic point-of-care tests vs the current standard of care for the management of cardiac surgery patients at risk of coagulopathic bleeding. Randomized controlled trials comparing viscoelastic point-of-care diagnostic testing with standard care in cardiac surgery patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
127
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 29 publications
1
127
0
1
Order By: Relevance
“…26 Identification of patients with bleeding diathesis is a cornerstone of pointof-care management of perioperative bleeding, but there is a lack of evidence of its efficacy in reducing the risk of re-exploration for excessive bleeding. 27 Indeed, preoperative thromboelastometry may fail to predict severe bleeding due to surgical site bleeding. 25 The results of this pooled analysis suggest that severe bleeding indicating reoperation for surgical hemostasis is related to surgical site bleeding in two-thirds of patients undergoing adult cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…26 Identification of patients with bleeding diathesis is a cornerstone of pointof-care management of perioperative bleeding, but there is a lack of evidence of its efficacy in reducing the risk of re-exploration for excessive bleeding. 27 Indeed, preoperative thromboelastometry may fail to predict severe bleeding due to surgical site bleeding. 25 The results of this pooled analysis suggest that severe bleeding indicating reoperation for surgical hemostasis is related to surgical site bleeding in two-thirds of patients undergoing adult cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, coagulation itself is complex with no global indices capable of assessing all the components that contribute to or inhibit clot formation. Several studies have investigated the effect of using ROTEM indices on clinical endpoints such as blood loss, blood transfusion, and bleeding complications (or a combination) during and after major surgery, and these have been subject to systematic reviews [27][28][29] . Most of these reviews have shown a benefit of using ROTEM measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, in none of the studies has it been possible to exclude bias. For this reason, while many professional bodies and organisations recommend the use of viscoelastic measurements during major procedures associated with extensive blood loss, the level of recommendation is typically B or C [27][28][29] . Under these circumstances, studies assessing the ability of ROTEM indices to identify particular coagulation defects, rather than outcome per se, may increase the confidence with which clinical decisions are made 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings confirmed that only a high age and D-dimer among standard laboratory tests appeared to BE differentbetween non-survivors and controls. Therefore, we investigated the use of thromboelastometry (RO-TEM ® ) in sepsis, a promising point-of-care test that was shown to be effective as a rapid global assessment of hemostasis in wholeblood samples, allowing the assessment of each stage of the coagulation process in bleeding patients [21][22][23][24]. We also examined the potential correlation between a higher risk of short-term death and severe hypocoagulability.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to confirm that both non-survivors at 28 days (Group A) and non-survivors between days 29 and 90 (Group B) exhibited more hypocoagulable profiles compared to Survivors (i.e., longer CT, longer CFT, and reduced MCF and TDI in the EXTEM assay). These parameters have been widely studied in the literature, and each parameter measures a specific phase of the coagulation cascade which is differently influenced by coagulation factors, fibrinogen, platelets, or the fibrinolytic system [18,[22][23][24]. However, the prognostic value of these parameters remains unclear.…”
Section: Discussionmentioning
confidence: 99%